Alkenones in Pleistocene Upper Bed I (1.803–1.900 Ma) sediments from Paleolake Olduvai, Tanzania. (August 2022) - Brassell, Simon C.; Colcord, Devon E.; Shilling, Andrea M.; Stanistreet, Ian G.; Stollhofen, Harald; Toth, Nicholas; Schick, Kathy D.; Njau, Jackson K.; Freeman, Katherine H.
Highlights: C37 to C40 alkenones occur in Pleistocene sediments from Paleolake Olduvai. Alkenone distributions do not contain tetraunsaturated components. Alkenones derive from Group II haptophytes during both wetter and drier intervals. Temporal profiles for unsaturation indices reflect lake salinity/alkalinity. Abstract: The Olduvai Gorge Coring Project (OGCP) recovered sequences of Pleistocene lake sediments that correlate with those known from outcrops directly associated with hominin fossil horizons. The sedimentary succession from Core 2A (02° 58′ 43′' S, 035° 19′ 25.5′' E), which targeted the ancient lake-basinal depocenter, includes stratigraphic intervals (∼1.86 Ma) sandwiched between the Bed I basalt and Tuff IF dated horizons, where remains of two hominin holotypes have been recovered. The lower part of this sequence (72.3–86.9 mbs) consists of lacustrine claystones interbedded with sandy claystones characterized by high Corg (av. 2.5%) and includes several laminated intervals. It displays shifts in terrestrial vegetation recorded by values for δ 13 CTOC and δ 2 HnC31 that reflect changes in the proportions of C3 vs C4 plants and precipitation, respectively. These temporal profiles represent higher-resolution signatures of the precession-scale wet/dry cycles previously recognized in the outcropping sedimentary succession of Olduvai Gorge. Several samples from this interval contain alkenones comprising C37 and C39 alkadien-2-ones and alkatrien-2-ones, and C38 and C40 alkadien-3-ones and alkatrien-3-ones. They are distinguished from the vast majority of alkenone distributions reported in lake sediments from polar and temperate latitudes (e.g., Greenland, N. and S. America, Europe, Russia, China, S. Africa, Antarctica) by the absence of tetraunsaturated alkenones (e.g., C37:4 ). The alkenone distributions vary stratigraphically with higher concentrations in the drier intervals of the precession-scale cycles that exhibit characteristics resembling those of Group II haptophytes found in contemporary saline/alkaline environments rather than those of Group I haptophytes from freshwater ecosystems. Paleolake Olduvai represents the first reported occurrence of alkenones in a low-latitude Pleistocene lake, where the absence of alkatetraenones may reflect contributions from strains of Group II haptophytes that are favored by warmer temperatures or saline conditions. Temporal variations in unsaturation indices ( U 37 K', U 38 K' ) and the proportions of alken-2-ones and alken-3-ones likely reflect influences on alkenone production by haptophytes that are associated with changes in the lake environment primarily driven by hydrologic cycles (e.g., salinity and alkalinity) rather than lake temperatures.